PENGARUH RASIO KEUANGAN TERHADAP HARGA SAHAM PERUSAHAAN UNGGULAN (Studi Empiris Pada Perusahaan yang Konsisten Masuk dalam Indeks LQ45 Tahun 2015-2017) - Winda Wijayanti; Paulus Th Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2019)
This study aims to examine the fundamental effect of financial performance through financial ratios such as liquidity with proxy current ratio (CR), solvency with the proxy total debt to common equity (TDCE), activity with asset turnover (AT) proxy, and profitability with a proxy for return on assets (ROA) on the company's stock price. The data population of this study is companies that consistently entered the LQ45 index in a row in the 2015-2017 period listed on the Indonesia Stock Exchange. This research sample numbered 35 companies obtained by purposive sampling with accumulation of data as much as 105 data which was then reduced by 11 outliers, thus amounting to 94 data. This study uses the analytical method used is multiple regression which is processed with the SPSS application. The results of the t-test statistics show that CR and TDCE have a negative and significant effect on stock prices, AT has a positive and significant effect on stock prices, and ROA has no effect on stock prices.